A Quantitative Analysis of the Work Experiences of Adults with Visual Impairments in Nigeria. (November 2013) - Wolffe, Karen E.; Ajuwon, Paul M.; Kelly, Stacy M.
Introduction: Worldwide, people with visual impairments often struggle to gain employment. This study attempts to closely evaluate the work experiences of employed individuals with visual impairments living in one of the world's most populous developing nations, Nigeria. Methods: The researchers developed a questionnaire that assessed personal and professional experiences among a sample of 172 adults with visual impairments living and working in Nigeria. Statistical analysis procedures included descriptive and nonparametric methods. The Mann-Whitney U test compared the difference between the mean ranks of 12 work-experience measures (dependent variables) within the independent groups. Results: Gender, degree of visual impairment (total blindness or low vision), age at onset of visual impairment (childhood or adulthood), educational attainment, and marital status were all characteristics that evidenced significant differences (p <.05) in the participants' work experiences evaluated by the present study. However, there were also instances where there were no significant differences in the independent groups among several of the 12 work-experience measures (p > .05). Discussion: Annual income, hours worked per week, confidence level performing current work, and future job opportunities were found to be significant based on participants' gender, education, or marital status. There was overall consistency among participants in the sample (regardless of degree of visual impairment or age at onset of visual impairment). Implications for practitioners: In this sample, advanced education equated to higher salaries and greater confidence in performing work. The importance of postsecondary education was affirmed in terms of future earnings and confidence.